Protocolo Híbrido de Ordem Total Uniforme com entrega Optimista - Vicente, Pedro (2001)
Broadcast algorithms with total uniform order simplify the development of applications that use replication as a fault-tolerance technique. This paper presents and compares three alternatives to implement an optimistic delivery service in total order uniform broadcast protocols for large-scale systems.